Formulation and evaluation of antioxidant activity of lip moisturizing serum containing dragon fruit pulp extract (Selenicereus monacanthus (Lem.) D.R.Hunt) and avocado pulp oil (Persea americana Mill.) - Ade Irfan; Shelly Taurhesia; Kosasih (JURNAL ILMU KEFARMASIAN INDONESIA, 2026)
This study aimed to formulate and evaluate a lip moisturizing serum containing dragon fruit extract (Selenicereus monacanthus (Lem.) D.R.Hunt) and avocado oil (Persea americana Mill.) with a focus on antioxidant activity, moisturizing efficacy, irritation potential, and physical stability. The combination of both ingredients was optimized at a 2:1 ratio of extract to oil, which exhibited the highest antioxidant activity. Based on this ratio, three serum formulations were developed: F0 (placebo), F1 (100×), and F2 (200×). The formulations were evaluated for their physicochemical properties, antioxidant capacity, moisturizing performance, irritation response, and stability using a cycling test. The results demonstrated that the antioxidant activity decreased after formulation but remained strong for F1 and F2 after formulation. Among all formulations, F2 exhibited optimal characteristics - strong antioxidant effect, high moisturizing ability, stable physicochemical properties, and no signs of irritation. These findings indicate that the 2:1 combination of dragon fruit extract and avocado oil can be successfully developed into a stable, effective, and antioxidant-rich natural lip-moisturizing serum.